Pulmonary Hypertension with Prolonged Patency of the Ductus Arteriosus in Preterm Infants - Ranjit Philip; Vineet Lamba; Ajay Talati; Shyam Sathanandam (MDPI AG, 2020)
There continues to be a reluctance to close the patent ductus arteriosus (PDA) in premature infants. The debate on whether the short-term outcomes translate to a difference in long-term benefits remains. This article intends to review the pulmonary vasculature changes that can occur with a chronic hemodynamically significant PDA in a preterm infant. It also explains the rationale and decision-making involved in a diagnostic cardiac catheterization and transcatheter PDA closure in these preterm infants.